Global burden of disease for musculoskeletal disorders in all age groups, from 2024 to 2050, and a bibliometric-based survey of the status of research in geriatrics, geriatric orthopedics, and geriatric orthopedic diseases - Fan Jiang; Conglan Lu; Zhen Zeng; Zhongyang Sun; Yang Qiu (Journal of Orthopaedic Surgery and Research)
Abstract Background Orthopaedic diseases in the elderly pose a significant disease burden, and the number of research papers on the subject is increasing every year. Methods The GBD database was used to analyze the global disease burden of musculoskeletal disorders in all age groups from 2024 to 2050. The source for bibliometrics was the WoSCC SCI-E database. Results Global disability-adjusted life years (DALYs) for musculoskeletal disorders by age were dominated by those aged 70 years and older, but the rate of change in DALYs between 2024 and 2050 was approximately ± 1%. We performed a descriptive analysis of 164,521 geriatrics articles, and 7155 geriatric orthopedics and geriatric orthopedic articles, and performed clustering, co-citation, collaborative network, and burst citation analyses based on Citespace and VOSviewer. Seven clustering tags containing hot content and 26 burst citation keywords containing hot content were finally targeted. Conclusion DALY in older adults over 70 years of age accounts for a significant portion of the disease burden of musculoskeletal disorders. Possible future research hotspots in geriatric orthopedics and geriatric bone diseases include three directions: (1) novel clinical procedures and postoperative management (2) various comorbidities caused by SARS-CoV-2 infections and other pathogens; and (3) effectiveness of Stem Cell Therapy in Clinical Applications and Biological Mechanisms of Stem Cell Therapy.